2019
DOI: 10.3889/oamjms.2019.088
|View full text |Cite
|
Sign up to set email alerts
|

Templating Hip Arthroplasty

Abstract: BACKGROUND: Different methods have been developed and employed with variable degrees of success in pre-operative templating for total hip arthroplasty. Preoperative templating, especially digital templating, has been claimed to have increased the effectiveness of total hip arthroplasty by improving the precision of prediction of prosthetic implant size. AIMS: The overall aim of this systematic review is to identify whether the use of pre-operative templating in total hip arthroplasty procedures has resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 51 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…These figures certainly stressed that an experienced hand also has a significant role to play inaccurate preoperative templating. 24 Similarly, it has been found that the training and experience levels of the attending surgeon have no effect on the accuracy of acetabular component templates, but these factors do have a serious impact in determining the accuracy and precision of the femoral component template.…”
Section: Discussionmentioning
confidence: 99%
“…These figures certainly stressed that an experienced hand also has a significant role to play inaccurate preoperative templating. 24 Similarly, it has been found that the training and experience levels of the attending surgeon have no effect on the accuracy of acetabular component templates, but these factors do have a serious impact in determining the accuracy and precision of the femoral component template.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a reflection of the relatively small number of cases in the study. In a recent systemic review, preoperative templating resulted in a significant increase in the accuracy of THA [ 21 ]. However, the exclusive dependence on templating resulted in correct size-matching in only up to 60% of cases in other previous studies [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…THA is now the gold standard procedure for orthopedic patients with extensive hip joint pathologies such as developmental dysplasia of the hip [ 3 ] and end-stage hip osteoarthritis [ 4 ]. Although the most common indication of THA is osteoarthritis, the procedure is also indicated for the management of displaced fracture of the femoral neck in younger patients, juvenile rheumatoid arthritis, ankylosing spondylitis, hip fractures, bone tumors (benign and malignant), arthritis that is associated with Paget’s disease, and unreduced traumatic dislocation of the hip joint [ 5 ].…”
Section: Introductionmentioning
confidence: 99%